IMPLEMENTASI CERTAINTY FACTOR PADA APLIKASI PSIKOLOGI REMAJA BERBASIS ANDROID - Astuti, Reny Wahyuning; Kahar, Novhirtamely; Widiantara, Ary (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2019)
The presence of information technology applications programs to assist and play an important role in human life, especially in the world of work. One application of an expert system program, which is a computer-based system that uses knowledge, facts and reasoning techniques in solving a problem that usually can only be solved by an expert in the field of knowledge. One application of expert systems based on android especially a psychologist in the field of child psychology problems. Where the child is to live a happy period and without sin, but what happens if we have children growing up is not good, especially in the development of feelings, behaviors, and emotions that can be changed or not subject to fixed. The problem has resulted in the development of normal parents worried about the construction or emotional disturbances that occur on their children. Concerns that make parents become confused about what to do and how to deal with this problem, for parents who are not necessarily able to handle a serious problem that requires a child experts called